Sustainable Mortar Made with Local Clay Bricks and Glass Waste Exposed to Elevated Temperatures - Zaid Ali Hasan; Shereen Qasim Abdulridha; S. Z. Abeer (Salehan Institute of Higher Education, 2021)
The present study involved assessing the replacement of fine aggregate in the mortar with sustainable local materials like clay bricks and glass included 168 specimens (cubes and prisms). Seven mixtures were cast for this work, one control mix (R1) with 100% natural sand whereas mixes from R2 to R5 have 10% and 20% replacing natural sand with waste clay bricks and waste glass separately and respectively. Mix R6 was included 20% replacing sand with combination waste materials (10% waste clay bricks with 10% waste glass). Mix R7 has involved the same percent of replacing the previous mix R6 but with adding Polypropylene fibers 1% by volume. The samples have put in an electrical oven for one hour at 200, 400, and 600 ᵒC then cooled to room temperature to be tested and compared with samples at normal temperature 24 ᵒC. Different mechanical tests were adopted involved flow tests, density, weight loss, compressive strength, flexural strength, and water absorption. The results at different temperatures were discussed where many findings were specified. The flexural strength at 400 ᵒC was showed improving by 56% for 20% waste clay brick and 69% with 10% waste glass, as well all combination mixes illustrated higher strength than the control. Doi: 10.28991/cej-2021-03091729 Full Text: PDF